Association of VCAM-1 overexpression with oncogenesis, tumor angiogenesis and metastasis of gastric carcinoma - Ding, Yong-Bin (World J Gastroenterol, 2003)
AIM: To investigate the relationship between the expression of vascular cell adhesion molecule-1 (VCAM-1) and oncogenesis, tumor angiogenesis and metastasis in gastric carcinoma, and to evaluate the clinical significance of serum VCAM-1 levels in gastric cancer. METHODS: Specimens from 41 patients with gastric cancer, 8 patients with benign gastric ulcer, and 10 healthy subjects were detected for the expression of VCAM-1 by immunohistochemistry. Microvessel density (MVD) was measured by counting the endothelial cells immunostained with the monoclonal antibody CD34 at × 200 magnification. Serum VCAM-1 concentrations were measured by an enzyme linked immunosorbent assay in the 41 gastric cancer patients before surgery, and at 7 d after surgery as well as in 25 healthy controls. The association between preoperative serum VCAM-1 levels and clinicopathological features, and their changes following surgery was evaluated. In addition, serum carcinoembryonic antigen (CEA) was also examined. RESULTS: Of the 41 gastric cancer tissues, 31 (75.6%) were VCAM-1 positive. The VCAM-1 positive gastric cancers were more invasive and classified in the more advanced stage than the VCAM-1 negative ones. The VCAM-1 positive cancers were associated with more lymph node metastases than VCAM-1-negative ones (P < 0.05). The expression of VCAM-1 was detected in tissues of two of the eight patients with gastric ulcer and two of the 10 healthy controls. The expression of VCAM-1 in gastric cancer patients was significantly more frequent than that in the healthy controls and ulcer group (both P < 0.05). MVD in VCAM-1 expressing tissues was higher than that in VCAM-1 negative tissues (t = 2.13, P < 0.05). Serum VCAM-1 levels in gastric cancer patients were significantly higher than those in controls (t = 3.4, P < 0.05). There was a significant association between serum VCAM-1 levels and disease stage, as well as invasion depth of the tumor and the presence of distant metastases. The concentrations of serum CEA in gastric cancer were higher than normal controls. Both serum VCAM-1 and CEA levels decreased significantly after radical resection of the primary tumor (P < 0.05). Furthermore, the serum levels of VCAM-1 were positively correlated with the expression of VCAM-1 in the tumor tissue (r = 0.85, P < 0.05). CONCLUSION: The expression of VCAM-1 is closely related to oncogenesis, tumor angiogenesis and metastasis in gastric carcinoma. Serum VCAM-1 level in gastric cancer patients is significantly increased compared with normal controls, which decreases significantly after radical resection of the primary tumor. The serum concentration of VCAM-1 may be considered as an effective marker of tumor burden of gastric cancer. Moreover, overexpression of VCAM-1 in gastric cancer tissue is likely a major source of serum VCAM-1.